Islam Ditinjau dari Berbagai Aspeknya - Kasiono; Muhammad Amri; Indo Santalia (CV Putra Publisher, 2023)
Islam is the Religion of Allah revealed to the Apostles as guidance and mercy of Allah for mankind at all times, which ensures the welfare of material and spiritual life, worldly and hereafter. Islam, namely the religion of Islam brought by the Prophet Muhammad as the prophet of the end of time, is a teaching revealed by Allah which is contained in the Qur'an and the authentic Sunnah of the Prophet (maqbul) in the form of commands, prohibitions, and instructions for goodness. human life in this world and the hereafter. Islamic teachings are comprehensive which cannot be separated from one another covering the fields of aqidah, morality, worship, and mu'amalah mu'amalah. Islam is a religion for surrender solely to Allah, the religion of all the prophets, a religion that is in accordance with human nature, a religion that is a guide for humans, a religion that regulates human relations with God and human relations with others, a religion that is a blessing for humans. universe. Islam is the only religion that is acceptable to Allah and the perfect religion.